REKSA DANA SYARIAH - SITI KHALIDJAH (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2017)
Sharia mutual funds are mutual funds operated by an investment company thatcollects money from shareholders and invests in stocks, bonds, options,commodities or money market securities that are operational according to thesyariah requirements and principles. In investing and managing mutual fundsalmost the same as other bank institutions. Starting from filling out the form tofollow the rules that are issued by the agency. The development of this mutualfund from year to year experienced a better improvement and the addition ofsharia mutual fund institutions.